Preparedness of the Bantul District Regional Disaster Management Agency for the tsunami at Parangtritis Beach, Indonesia - Kharimah, Islamia; Legowo, Endro; Bangun, Ernalem; Widana, I Dewa Ketut Kerta (Technium Social Sciences Journal, 2022)
The subduction zone in southern Java Island causes areas in the south of Java Island prone to tsunami disasters. Bantul District is located in south of Java Island. Parangtritis Beach in Bantul District has the highest number of visitors than other beaches in D.I.Yogyakarta Province. As an area visited by many local and foreign tourists, preparedness needs to offer to local communities and tourists. In order to when a disaster occurs, there are not many casualties, both from local communities and tourists. This study uses parameters from LIPI-UNESCO/ISDR (2006). The result of this study is that the preparedness of the Regional Disaster Management Agency of Bantul Regency to face the tsunami disaster has an index value of 93.99 which means it is very ready. However, preparedness effort has not been carried out optimally and thoroughly. Preparedness is still a priority for the local community and has not prioritized tourists.